MCM-41-supported vanadium catalysts structurally modified with Al or Zr for thiophene hydrodesulfurization - Escalante Contreras, Yelisbeth Carolina (2019)
Vanadium catalysts supported on Al(Zr)-MCM-41-type materials were prepared by impregnation. Textural and structural properties, elemental composition and electronic structure were determined by N2 physisorption, small-angle XRD, SEM?EDX and UV?vis DRS, respectively. Al-containing materials showed mostly of Al framework and a small fraction of Al extra-framework species. Zr-containing materials presented almost exclusively small clusters of ZrxOy covering the MCM-41 matrix. Vanadium catalysts, showed the presence of isolated V5+ species and to a lesser extent polymeric chains likely as small crystallites of V2O5. The catalytic results revealed that VAlM30 catalyst, characterized by a Si/Al atomic ratio of 30, was the most active in thiophene hydrodesulfurization, which could be associated to better textural properties and high dispersion of the vanadium species.